2015
DOI: 10.1007/s10900-015-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

A Smoke-Free Community Housing Policy: Changes in Reported Smoking Behaviour—Findings from Waterloo Region, Canada

Abstract: In 2010, Waterloo Region Housing (Canada) enacted a smoke-free (SF) housing policy that made all new leases in their community-housing portfolio (2722 units) 100 % SF. Existing lease holders were 'grandfathered'-meaning tenants could still smoke in their homes. A survey to measure support for the policy and how the policy had impacted smoking behaviour was delivered to all 2722 households in the Waterloo Region Housing portfolio in 2010 (pre-policy), 2011 and 2013 (post-policy). The proportion of households th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
3
25
0
1
Order By: Relevance
“…In partnership with ROWPH, free cessation support services were offered to tenants. ( McCammon-Tripp and Stitch, 2010 ; Kennedy et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…In partnership with ROWPH, free cessation support services were offered to tenants. ( McCammon-Tripp and Stitch, 2010 ; Kennedy et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, people in the hamlet have the characteristic of being easy to receive new knowledge that is considered beneficial so that when the SFH initiative was introduced, the reception was welcoming. Even smokers supported the SFH initiative because they were aware of the dangers for their loved ones 12 . This is indicated by the relatively small (19%) proportion of smokers who smoked near family members in the hamlet compared, for instance, with Bantul district with 68% 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The SFH initiative has been developed in several countries, but the results vary. Experiences in high-income countries show that SFH is an effective means of reducing levels of cigarette consumption and increasing the likelihood of quitting smoking [11][12][13] . Experiences in LMICs such as India and Indonesia, especially in urban areas, indicate that the SFH initiative reduces smoking behaviour in homes and increases smokers' readiness to stop smoking [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that more than half of the smokers had decreased their smoking amount since the policy was implemented, while 14.7% of the smokers had succeeded in quitting 5 . Since the smoke-free housing policy was implemented in Waterloo, Canada, about a third of smokers therein reported a decrease in their cigarette consumption 6 .…”
Section: Discussionmentioning
confidence: 99%